ดง ฌวงกับพฤติกรรม "ซาดิสม์" - พิริยะดิศ มานิตย์ (คณะมนุษยศาสตร์ มหาวิทยาลัยเกษตรศาสตร์, 2009)
This paper provides a psychoanalytic interpretation of Moliere s Dom Juan. It seeks to make sense of Dom Juan s characters, and finds that the hero has a behavioral pattern that implies a sadistic tendency, or pleasure of inflcting pain